2021
DOI: 10.1088/2632-959x/abe990
|View full text |Cite
|
Sign up to set email alerts
|

Point Defects in InGaN/GaN Core–Shell Nanorods: Role of the Regrowth Interface

Abstract: Core-shell nanorod based light-emitting diodes (LEDs) with their exposed non-polar surfaces have the potential to overcome the limitations of planar LEDs by circumventing the quantum confined stark effect. In this experiment, InGaN/GaN core-shell nanorods were fabricated by a combination of top-down etching and bottom-up regrowth using metal-organic vapour phase epitaxy. When viewing the nanorods along their long axis, monochromatic cathodoluminescence maps taken at the GaN near-band-edge emission energy (3.39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The sample is then coated with a 25 nm thick Ni layer by metal evaporation (Pfeiffer classic 500) and mask lift-off is eventually performed with the remover AR600-71 for 60 min. The obtained Ni pattern will be used as a hard mask for the subsequent chlorine-based plasma etching [37][38][39][40][41][42][43]. The nonprotected part of the SiN x layer is first reactively etched in CF 4 /O 2 at a plasma power of 50 W and pressure of 4 Pa (Sentech SI 500).…”
Section: Top-down Nw Fabricationmentioning
confidence: 99%
“…The sample is then coated with a 25 nm thick Ni layer by metal evaporation (Pfeiffer classic 500) and mask lift-off is eventually performed with the remover AR600-71 for 60 min. The obtained Ni pattern will be used as a hard mask for the subsequent chlorine-based plasma etching [37][38][39][40][41][42][43]. The nonprotected part of the SiN x layer is first reactively etched in CF 4 /O 2 at a plasma power of 50 W and pressure of 4 Pa (Sentech SI 500).…”
Section: Top-down Nw Fabricationmentioning
confidence: 99%
“…7,8 Their fabrication varies from top-down, 9,10 bottom-up, 11,12 or hybrid methods. 13,14 Transistors are mainly covered by the first method and, in numerous cases, such as for current aperture vertical electron transistors (CAVETs) and metal-oxidesemiconductor field-effect transistors (MOSFETs), by a combination of etching and regrowth by metal−organic vapor phase epitaxy (MOVPE). 15−17 On the other hand, the development of 3D structures solely by growth has been frequently applied for optoelectronic devices targeting microLED displays and the visible light communication market, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The need of miniaturizing devices to satisfy the demands of new opto- and power electronics applications has prompted research on three-dimensional (3D) GaN-based structures. Using these architectures enables the increase of active area per wafer footprint, the use of nonpolar facets free of QCSE, as well as the decrease of dislocation densities, features that are highly desirable in optoelectronic devices. ,, In terms of power electronics, 3D microstructures may enable better electrostatic control over the channel, subdue the leakage current, reduce strain, and increase breakdown voltage. , Their fabrication varies from top-down, , bottom-up, , or hybrid methods. , Transistors are mainly covered by the first method and, in numerous cases, such as for current aperture vertical electron transistors (CAVETs) and metal-oxide-semiconductor field-effect transistors (MOSFETs), by a combination of etching and regrowth by metal–organic vapor phase epitaxy (MOVPE). On the other hand, the development of 3D structures solely by growth has been frequently applied for optoelectronic devices targeting microLED displays and the visible light communication market, among others …”
Section: Introductionmentioning
confidence: 99%
“…39,40 In addition, the MQS on the (0001) plane region is bothered by serrated and rough surfaces, which are regarded as a source of current leakage. 18,41,42 The IQE of NW-LEDs is generally reported to be in the range of 5−30%, as measured by temperature-dependent photoluminescence. 22,43−45 This range is relatively lower than that of conventional (0001) c-plane LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the periodic arrangement of NWs and the core–shell structures, the fabrication can reduce the degradation of EQE. Nevertheless, the crystalline quality of MQS NW remains limited by the high density of point defects due to the high growth temperature and low V/III ratio for n-GaN core NW growth. , In addition, the MQS on the (0001) plane region is bothered by serrated and rough surfaces, which are regarded as a source of current leakage. ,, The IQE of NW-LEDs is generally reported to be in the range of 5–30%, as measured by temperature-dependent photoluminescence. , This range is relatively lower than that of conventional (0001) c -plane LEDs. , One effective approach to suppress the point defects and improve the performance of conventional LEDs is the introduction of superlattice (SL) structures prior to the MQW growth. It has been reported that the IQE of the (0001) plane LEDs with an SL can be increased by about 20% under a current injection density of 300 A/cm 2 , and the electroluminescence (EL) intensity can be increased by about three times through the application of SL structures. , It is believed that the SL increases the performance of (0001) plane LEDs by trapping point defects that can easily diffuse toward the active region during growth .…”
Section: Introductionmentioning
confidence: 99%